Panorama of teaching in higher education institutions under science, technology, engineering and mathematics (STEM) programs - Oliveros Ruiz, Maria Amparo (Revista Científica, 2021)
Student enrolment in science, technology, engineering and mathematics (STEM) programs is critical in Mexico. Mexican employers reported having difficulty finding people with the necessary skills to fill vacancies in STEM areas. Our study analysed student responses regarding the main factors in choosing a STEM career. These included everything from gender roles to family opinions. The resulting indicators showed how cultural training, youth identity and gender equity impact career choices related to STEM for students in Mexico’s border areas of Baja California and Sonora. Our results can help define strategies universities should implement and success factors for recruiting and retaining students in STEM programs.